(untitled) (Лучшие интеллектуальные исследования, 2025)
This article explores the stylistic differences between Uzbek and English languages, focusing on how cultural, historical, and linguistic factors shape stylistic choices in both languages. It discusses the unique characteristics of each language’s stylistic devices, including metaphor, simile, and idiomatic expressions. The article highlights the implications of these differences for translation, language learning, and cross-cultural communication.